2014
DOI: 10.1186/1471-2407-14-540
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation of unresectable soft tissue tumors with vascular invasion: effective palliation

Abstract: BackgroundIrreversible electroporation (IRE) has recently been added as an additional therapeutic ablative option in patients with locally advanced cancers (LAC) involving vital structures. IRE delivers localized electric current by peri-tumoral discrete probes to attain irreversible changes in cell membrane leading to cell death. The aim of this study was to evaluate the long-term effects of IRE in the treatment of locally advanced tumors.MethodsA prospective IRB approved evaluation of 107 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 21 publications
(28 reference statements)
0
35
1
Order By: Relevance
“…For these reasons, IRE is an attractive treatment option for various soft tissue tumors located in challenging locations [3].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, IRE is an attractive treatment option for various soft tissue tumors located in challenging locations [3].…”
Section: Introductionmentioning
confidence: 99%
“…This unique method of action has allowed for IRE to be successfully utilized in the palliative treatment of LAPC safely, with surprisingly prolonged survival. 1,2,6,7 Recent advances in multimodality therapy of stage 3 LAPC have included chemotherapy, surgery, and/or radiation therapy. Surgical resection of LAPC in combination with multimodality treatment remains the optimal treatment option based on the improved overall survival in reported cases.…”
mentioning
confidence: 99%
“…Several studies on the in vivo potential applications of IRE for solid tumors (e.g., lung, liver, kidney, and pancreas) have been published [17,18,19,20,21,22,23]. Martin et al showed that IRE is a suitable option for LAPC with encouraging preliminary results in terms of safety and feasibility, local-progression-free survival, distant progression-free survival and overall survival [24,25].…”
Section: Introductionmentioning
confidence: 99%